Biological age: problems and prospects. Literature review - S. A. Berns; A. A. Savicheva; O. Yu. Isaykina; A. V. Veremeev; A. Yu. Gorshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Biological age has attracted increased attention of the medical community in recent years. It is individual for each person and currently there is no clear classification for dividing into groups that could help determine whether the rate of aging in a particular individual is normal or pathological. Today, scientists are conducting a large number of clinical and laboratory studies to find the optimal marker of biological aging that would meet all the requirements. The review aim is to analyze and summarize the available data on the mechanisms of aging, the development of novel markers of biological aging and calculators that can be used in routine practice in the future to prevent the development and progression of noncommunicable diseases.